2019
DOI: 10.1007/s10344-019-1332-0
|View full text |Cite
|
Sign up to set email alerts
|

Backpack-mounted satellite transmitters do not affect reproductive performance in a migratory bustard

Abstract: Backpack-mounted satellite transmitters (PTTs) are used extensively in the study of avian habitat use and of the movements and demography of medium-to large-bodied species, but can affect individuals' performance and fitness. Transparent assessment of potential transmitter effects is important for both ethical accountability and confidence in, or adjustment to, life history parameter estimates. We assessed the influence of transmitters on seven reproductive parameters in Asian houbara Chlamydotis macqueenii, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Each was fitted with a backpack harness-mounted satellite transmitter (Microwave Telemetry Argos/global positioning system [GPS] Platform Transmitter Terminal [PTT]-100, either 30 [both sexes] or 45 g [males only] models) that recorded 5 to 12 GPS fixes per day. Transmitters weighed <3% of body mass (females = 1.25 kg ± 0.15 SD; males = 1.82 kg ± 0.31 SD weights at capture) and do not affect breeding performance (39), so they are assumed to have minimal or no effect on migration.…”
Section: Methodsmentioning
confidence: 99%
“…Each was fitted with a backpack harness-mounted satellite transmitter (Microwave Telemetry Argos/global positioning system [GPS] Platform Transmitter Terminal [PTT]-100, either 30 [both sexes] or 45 g [males only] models) that recorded 5 to 12 GPS fixes per day. Transmitters weighed <3% of body mass (females = 1.25 kg ± 0.15 SD; males = 1.82 kg ± 0.31 SD weights at capture) and do not affect breeding performance (39), so they are assumed to have minimal or no effect on migration.…”
Section: Methodsmentioning
confidence: 99%
“…However, previous studies on birds show that the amount of discomfort and time spent preening may increase (Robert et al ). However, studies have also shown non‐significant effect on reproductive success or foraging behavior as long as the transmitter load was low in relation to body weight (Phillips and Croxall , Burnside et al ). To minimize the potential effects of the transmitters, we kept transmitter weights < 3% of crane body weights (Phillips and Croxall ).…”
Section: Methodsmentioning
confidence: 99%
“…During the non-breeding season, transmitter attachment using this method has been shown to have little effect on behaviour, fat reserves, or hematological stress; the effects of attachment are generally absent or short-lived (primarily flight stability issues). 2531 All bird-handling protocols (WSU Permit #163) were approved by an institutional research advisory board with expertise in animal care. Radiotracking was accomplished using a portable, scanning VHF receiver (Model R410, Advanced Telemetry Systems, Isanti, MN, USA) fitted with a three-element Yagi antenna.…”
Section: Methodsmentioning
confidence: 99%